2021
DOI: 10.3390/vaccines9111224
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of CXC Motif Chemokine Ligand 10 (CXCL10) and Its Related Chemokines in the Pathogenesis of Coronary Artery Disease and in the COVID-19 Vaccination: A Narrative Review

Abstract: Coronary artery disease (CAD) and coronary heart disease (CHD) constitute two of the leading causes of death in Europe, USA and the rest of the world. According to the latest reports of the Iranian National Health Ministry, CAD is the main cause of death in Iranian patients with an age over 35 years despite a significant reduction in mortality due to early interventional treatments in the context of an acute coronary syndrome (ACS). Inflammation plays a fundamental role in coronary atherogenesis, atherosclerot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 120 publications
1
6
0
Order By: Relevance
“…A study presented by (Karimabad et al, 2021) for the coronary artery disease patients were found increase in the levels of IL-6 after second vaccination with a BNT162b2 mRNA (Pfizer/BioNTech) vaccine at day 2, and this study consistence with our finding of increased levels of IL-6 after 2 nd dose of Pfizer vaccine but at (20-30) days, and this confirm the association of IL-6 with the vaccination and will be resulting in antibody development.…”
Section: Interleukin 6 (Il-6)supporting
confidence: 89%
“…A study presented by (Karimabad et al, 2021) for the coronary artery disease patients were found increase in the levels of IL-6 after second vaccination with a BNT162b2 mRNA (Pfizer/BioNTech) vaccine at day 2, and this study consistence with our finding of increased levels of IL-6 after 2 nd dose of Pfizer vaccine but at (20-30) days, and this confirm the association of IL-6 with the vaccination and will be resulting in antibody development.…”
Section: Interleukin 6 (Il-6)supporting
confidence: 89%
“…We also constructed a protein-protein interaction network among differentially methylated and expressed genes (|log 2 FC| > 0.5, |diffMethy| > 0.1, and P < 0.05), in which CCL5 and CXCL10 were identified as the core genes of the network. CCL5 (chemokine ligand 5) and CXCL10 (CXC motif chemokine ligand 10) are chemokines responsible for facilitating inflammatory responses, including the adhesion and migration of different T cell subsets in immune responses, and are involved in various pathological processes including inflammation, chronic diseases, and cancers as well as the infection of COVID-19 (41,42). Interestingly, as key genes in the cytokine-cytokine receptor interaction signaling pathway, CCL5 and CXCL10 were also identified as core genes in our previous study in porcine aortic vascular endothelial cells infected with G. parasuis (19), and this prompted us to infer that these two chemokines may play a very important role in the immune response during G. parasuis infection and further study is necessary to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial gene CXCL10 encodes ligand that binds to CXCR3, resulting in monocyte stimulation, natural killer cells and T cells migration, and adhesion molecules expression. 33 In chronic periodontal disease, IL10 and IL6 contribute to the regulation of inflammatory cytokine secretion by macrophages in respond to bacterial stimulation. 34 When periodontal ligament fibroblasts were stimulated by bacteria, Tzach-Nahman et al 35 found increased IL6 production.…”
Section: Discussionmentioning
confidence: 99%